English for specific purposes corpora - Khamis, Noorli (Penerbit UTeM Press, 2024)
The growing emphasis on STEM (Science, Technology, Engineering, and Mathematics) and TVET (Technical and Vocational Education and Training) education in Malaysia has posed challenges to English language instructors in preparing learners to use English proficiently to meet industry demands. This task is further complicated by a lack of subject matter knowledge among language instructors. Consequently, they often rely on intuition or adopt existing English for Specific Purposes (ESP) resources for language teaching. This book offers a solution for ESP instructors to create meaningful teaching, learning, and assessment materials using ESP corpora (plural form for corpus). A corpus, a collection of electronic texts, serves various language teaching purposes, including for creating dictionary entries, designing language learning activities, and identifying learners' errors. The book guides beginner corpus users through the essential principles and steps for developing an ESP corpus, with a focus on practical approaches for language observations in ESP classrooms. Moreover, the author presents common applications of corpora for ESP, encouraging more ESP educators to incorporate corpora into their resources. This book targets English language instructors and researchers of technical universities, polytechnics, community colleges, vocational colleges, and technical secondary schools. It is also suitable for undergraduate and postgraduate students in TESL or English Studies programs at higher education institutions.